MODEL TESTING OF PILED CLUSTERS AND LARGE MONO-PILES OF IMPROVED DESIGN - Doubrovsky, M. P.; Dobrov, I. Yu.; Gerashchenko, A. V.; Dubrovska, O. M. (Academic journal Industrial Machine Building Civil Engineering, 2017)
When constructing piled clusters and structures supported by large mono-piles, piles designed are used to take up significant lateral and pressing-in loads. New effective and less resource-demanding design of piled cluster was considered before. At this paper some results of its model testing in laboratory conditions are analyzed and discussed. To increase energy-absorbing capacity of mooring/fender dolphins it was worked out and researched a new design of combined tubular mono-pile structure, incorporating internal flexible pile and damping element placed at the zone of pile head. This design has been tested by laboratory experiments using small scale model. Obtained results confirm its effectiveness and practicability.
Keywords: piled cluster; tubular mono-pile; bearing capacity; energy-absorbing capacity